Anti-Oxidative and Anti-Inflammatory Activity of Kenya Grade AA Green Coffee Bean Extracts - In-Chul LEE; Jae-Sook LEE; Jeong-Hyun LEE; Yeona KIM; Wi-Young SO (Tehran University of Medical Sciences, 2019)
Background: Kenya AA green coffee bean extracts were tested for natural ingredients used for anti-oxidative and anti-inflammatory purposes in cosmetic products. Methods: Anti-oxidative activities were measured by total polyphenol, 1,1-diphenyl-2-picrylhydrazyl (DPPH), and the 2,2'-azinobis (3-ethylbenzothiazoline-6-sulfonic acid) (ABTS) assays. Anti-inflammatory activities were evaluated via nitric oxide (NO) assays, and through quantification of inducible nitric oxide synthase (iNOS), and cyclooxygenase-2 (COX-2) protein expression by western blotting. Data analyses were performed using independent Student's t-tests, with statistical significance set at P < 0.05. Results: Total polyphenol content of water and ethanol extract was 169.0 ± 3.1 mg and 300.34 ± 16.6 mg tannic acid/g dry weight, respectively. The DPPH and ABTS radical scavenging activities of all the extracts were significantly increased in a concentration-dependent manner. Kenya AA green coffee bean extracts were toxic at a concentration of 1,000 µg/mL in RAW 264.7 cells. Anti-inflammatory activity as determined by NO assay showed that lipopolysaccharide (LPS)-induced NO was significantly inhibited following treatment with Kenya AA green coffee bean extracts in a concentration-dependent manner. iNOS and COX-2 protein expression was also significantly inhibited following treatment. Conclusion: These results highlight the potential of Kenya AA green coffee bean extracts as a naturally active anti-inflammatory agent in cosmetic products.